The Utilization of Best Practices and Contemporary Developments of Cost Accounting in Strategic Cost Management (International Journal of Financial, Administrative and Economic Sciences, 2023)
For harmonizing production processes and providing an effective production process in industrial enterprises, the first measure to be taken is to use contemporary developments that are appropriate for the structure of the enterprise. For industrial enterprises to be successful, the costing system in each production system should be determined and managed efficiently. Taking as a basis the cost management system is to help maximize the profit of the enterprise. To achieve this aim, contemporary enterprises should prepare for the future by constantly renewing themselves and competing under today’s circumstances. The fierce competition circumstances of today's world and the gradual shortening of the product life cycle compel enterprises to achieve their cost, time and quality objectives simultaneously. The said situation requires the enterprises to launch to market their products with a lower cost, higher quality and faster as compared to their competitors to meet the needs and demands of the customers, and this accomplishment can be realized by using modern costing systems in production.
Keywords: Cost; Contemporary Developments; Strategic Cost; Management